High‐Efficiency Low‐Temperature‐Processed Mesoscopic Perovskite Solar Cells from SnO2 Nanorod Self‐Assembled Microspheres. Issue 4 (30th January 2020) - Song, Jing; Li, Guodong; Wang, Deng; Sun, Weihai; Wu, Jihuai; Lan, Zhang
Abstract : Mesoporous scaffolds in perovskite solar cells (PSCs) can accelerate the formation of heterogeneous nucleation sites, leading to enhanced quality of perovskite films and uniform perovskite coverage over large areas. Nevertheless, the mesoporous electron transport layers (ETLs) can effectively compensate for the drawback of shorter electron diffusion lengths than their hole counterparts. Therefore, most mesoscopic PSCs usually show superior photovoltaic performance to their planar counterparts. However, mesoporous ETLs, particularly those prepared with metal oxide nanocrystals, often require a high‐temperature sintering process for the removal of residual organics and the improved crystallization of metal oxides. Here, a novel emulsion‐based bottom‐up self‐assembly strategy is used to prepare sizable SnO2 microspheres from oleic acid capped SnO2 nanorods. Combined with an in‐situ ligand‐stripping strategy, the low‐temperature solution‐processed mesoscopic PSCs can achieve efficiency as high as 21.35% with slight hysteresis and good reproducibility. In particular, the emulsion‐based bottom‐up self‐assembly strategy is a general way for preparing microspheres from several kinds of semiconductor nanocrystals, so it will greatly expand the material selection range for preparing efficient mesoscopic PSCs and even inverted mesoscopic devices. Abstract : A novel emulsion‐based bottom‐up self‐assembly strategy is used to prepare sizable SnO2 microspheres from oleic acid capped SnO2 nanorods. Combined with an in‐situ ligand‐stripping strategy, the low‐temperature solution‐processed mesoscopic perovskite solar cells (PSCs) can achieve an efficiency as high as 21.35% with slight hysteresis and good reproducibility. This novel route will greatly expand the material selection range for preparing efficient mesoscopic PSCs.